Hubungan Hipertensi dan Obesitas dengan Hipertensi Okular: Relationship between Hypertension and Obesity with Ocular Hypertension - Chair, Naila Permata; Fatmawati, Nur Khoma; Rachmi, Eva (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Intraocular pressure is the pressure inside the eye, which normally ranges from 10-21 mmHg, with an average of 16 ± 25 mmHg. Maintaining intraocular pressure within the normal range is crucial because elevated intraocular pressure (ocular hypertension) can lead to decreased perfusion in the eye which eventually increasing the risk of primary open-angle glaucoma (POAG) and retinal vein occlusion. High blood pressure and a high Body Mass Index (BMI) can influence an increase in intraocular pressure by disrupting the aqueous humor outflow mechanisms. The purpose of this study is to analyze the correlation between hypertension and obesity in ocular hypertension. The study employed an analytical observational design using a cross-sectional approach. Sample selection was performed using the purposive sampling method and involved 48 patients who met the study criteria. Researched data was obtained from both secondary and primary data through examination of blood pressure, body weight, height, and intraocular pressure. Bivariate data analysis was conducted using the Chi-Square test and Fisher's exact test. The results showed that the majority of the hypertensive patient group has normal intraocular pressure (41.6%), and the majority of obese patients also have normal intraocular pressure (43.7%). Based on bivariate analysis showed the correlation between hypertension and ocular hypertension yielded p-value = 0.458 and the correlation between obesity and ocular hypertension yielded p-value = 0.330. The analysis suggests that hypertension and obesity does not have a significant correlation with ocular hypertension. Keywords: Ocular Hypertension, Hypertension, Obesity, Intraocular Pressure Abstrak Tekanan intraokular merupakan tekanan di dalam bota mata, yang normalnya berkisar dari 10 – 21 mmHg, dengan rata-rata 16 ± 2,5 mmHg. Tekanan intraokular perlu dipertahankan dalam kisaran normal karena tekanan intraokular yang tinggi (hipertensi okular) memicu penurunan perfusi pada mata sehingga meningkatkan risiko terjadinya glaukoma sudut terbuka dan oklusi vena retina. Hipertensi dan indeks massa tubuh (IMT) tinggi dapat memengaruhi peningkatan tekanan intraokular melalui terganggunya mekanisme aliran humor aquos. Penelitian ini bertujuan untuk menganalisis hubungan antara hipertensi dan obesitas dengan hipertensi okular. Desain penelitian ini adalah observasional analitik dengan pendekatan cross-sectional. Pengambilan sampel dilakukan dengan metode purposive sampling dan melibatkan 48 pasien yang memenuhi kriteria penelitian. Data penelitian diperoleh dari data sekunder dan data primer melalui pemeriksaan tekanan darah, berat badan, tinggi badan, dan tekanan intraokular. Uji bivariat data dianalisis dengan uji Chi-Square dan Fisher’s Exact. Hasil penelitian menunjukkan mayoritas kelompok pasien hipertensi lebih banyak memiliki tekanan intraokular normal (41,6%) dan mayoritas pasien obesitas memiliki tekanan intraokular normal (43,7%). Berdasarkan analisis bivariat antara hubungan hipertensi dan hipertensi okular didapatkan p value = 0,616 dan hubungan obesitas dengan hipertensi okular didapatkan p value = 0,330. Dapat disimpulkan bahwa hipertensi dan obesitas tidak memiliki hubungan dengan hipertensi okular. Kata Kunci: Hipertensi Okular, Hipertensi, Obesitas, Tekanan Intraokular